Exploring police response and interaction with people with mental illness in Guyana. (25th November 2020) - Wallace, Wendell C.
ABSTRACT: In many developing countries, police officers are called upon to intervene in matters related to people with mental illness (PMI) and therefore constitute an important facet of pathways to medical care. Globally, police officers come into frequent contact with PMI and they (police) play a central role in the management of these individuals, however, police-PMI contact pose complex challenges for most police officers. Instructively, mental health professionals contend that police officers are not best suited to handle PMI and that many PMI are incarcerated, seriously injured or die as a result of their contact with the police. This study explores police officers' attitude, response and interaction with PMI in Guyana in order to assist with the development of appropriate interventions when policing PMI. The study utilises a random sample of police officers ( N  = 130) from the Guyana Police Force (GPF) to achieve the study's objectives. A modified variant of the Mental Health Attitude Survey for Police (MHASP) was used to garner the views of the participants. The findings indicate: (1) that a considerable amount of police time was spent dealing with PMI each week, (2) that contact with PMI pose considerable difficulties for police officers, (3) that the most common police interactions with PMI were investigations, arrests and conveying PMI to hospitals, (4) that police training on responding to PMI is insufficient, and (5) that mental health training can improve officers' ability to efficiently police PMI. Recommendations for training, directions for future research and policy implications are also discussed.